Harcourt science - Marjorie Slavick Frank et. al.; Robert Jones;Gerald Krockover;Mozell Land;Joyce McLeod;Carol Valenta;Barry Van Deman (Orlando, Florida : Harcourt School Publishers, 2000)
The world is made up of living things and non living things, All living things grow and change. They need food, water and air. Things that are not alive are non living things. They do not need food, water and air.
UnitA. Living Things Grow and Change -- UnitB. Homes for Living Things -- UnitC. Exploring Earth's Surface -- UnitD. Space and Weather -- UnitE. Exploring Matter -- UnitF. Energy and Motion .
Includes index.
Keywords: SCIENCE